The Impact of the Credit Risk of Loans Granted to Economic Sectors on the Overall Risk of the Bank Loan Portfolio (An Applied Study) (Journal of Hama University, 2021)
This study aims to determine the extent of the impact of the risks of loans granted to economic sectors (large companies, small and medium businesses, and individuals) in the overall risk of the bank loan portfolio, through an applied study of a sample of private commercial banks operating in Syria in the period 2010-2018.The descriptive approach was relied upon to achieve the aim of the study, and the data contained in the annual reports of the banks of the study sample were relied upon during the same period studied, and it was analyzed by relying on the combined regression model, Panel Data, to arrive at the mentioned results.The results of the study show that the risks of loans granted to large companies constitute the main reason behind the changes taking place in the totality of risk engulfing the loan portfolio of the sample banks. Figures show that these risks account for 52%, those of the loan granted to individuals for 19% and those of the loans granted to small and medium enterprises for 8% of the overall explanatory capacity of the given conditions